THE ONTOLOGY CONCEPT IN THE SEVEN DIGNITY AT-TUHFAH AL-MURSALAH WORKS OF BURHANFURI AL-HINDI - Mirza Mahbub Wijaya; Ahmad Yusuf Yusuf; Ahmad Muhdlori Muhdlori; Muchammad Nuryadi Nuryadi; Hadi Susilo Susilo; Muhamad Ansori Ansori (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Seven Dignity is one of the controversial teachings because it contains the thoughts of Waḥdat al-Wujud Ibn Arabi in it. Seven Martabat first time emerged from the Sufism text written by Muhammad Ibnu Syeikh Fadhlullah Al-Burhanfuri Al-Hindi, At-Tuhfah al-Mursalah Ila Ruh an-Nabiy, which is the material object of this research. This research is a literature review using philological and philosophical approaches. Meanwhile, the data analysis used content analysis. This book contains the seven divine dignity which is based on the philosophical thinking of Ibn Arabi. In the process of spiritual alignment with Khaliq, a salik must go through seven stages of dignity, namely 1. La Ta'ayyun's Dignity, 2. Early Ta'ayyun's Dignity, 3. Ta'ayyun Sani's Dignity, 4. 'Alam Al -'Arwah, 5. 'Alam Al-Misal,' 6. Alam Al-'Ajsam, and 7. 'Alam Al-'Insan. In it it is very identical with the Neoplatonic peripatetic view of the mind, making it part of God, and equating it with the attributes of God and Plato's World of Ideas..